Relative age effect on elite men's futsal according to region and playing position: A study of the FIFA Futsal World Cup Lithuania 2021 - de Oliveira Castro, H.; Figueiredo, L. Savassi; de Castro Ribeiro, L.; de Oliveira, V. [UNESP]; da Silva Aguiar, S.; Gomes, S. Adriano (Centro Andaluz de Medicina del Deporte, 2022)
Objective: To investigate the existence of relative age effect (RAE) in male futsal athletes that participated in the FIFA Futsal World Cup Lithuania 2021, according to region and playing position. Methods: The birthdates of 384 male futsal athletes participating in the competition were collected from official websites. Players were divided according to their continents and playing positions, and the chi-square goodness-of-fit tests ( 2) were performed to compare the expected and χ2) were performed to compare the expected and the observed birth the observed birthdate absolute distributions for each group. Also, specific effect sizes (ω) were calculated for each of the chi-square tests performed. Additionally, Odds Ratio (ORs) and 95% confidence intervals were calculated for the first and the last quarters of the year, as for semesters. Results: The overall analysis of the athletes indicated no presence of RAE in this sample, since an even distribution of birthdates was found (χ2) were performed to compare the expected and the observed birth2 = 5.949; p = 0.114; ω = 0.124). = 0.124). The regions analysed also indicated no presence of RAE. When playing positions were considered, once again analyses indicated no RAE to elite international futsal athletes, since no differences were found between the observed and expected birthdate distributions. Conclusion: RAE is not prevalent on the international male elite futsal context. This effect was not associated with region or playing positions. From a practical perspective, it is important that selection processes consider the incidence of the RAE and give similar opportunities to athletes regardless of their birthdate.
Keywords: Age Effect; Athletic Performance; Sports; Team Sports, Birth Registration